Vilniaus teisminė autonomija ir 1566 m. sausio 16 d. Žygimanto Augusto privilegija – savivaldos teisių garantas teismo reformos metu - Klovas, Mindaugas; Urmański, Antoni K. (Vilnius University Open Series, 2024)
In 1387, Jogaila’s privilege granted Vilnius the Magdeburg law and guaranteed the judicial autonomy of its citizens. Vilnius citizens had the right and the obligation to conduct their legal affairs in the courts of the Vaitas, the Bench judges and the Council, which started to function from the moment the privilege of self-governance was granted or shortly afterwards, and to be governed by Magdeburg law. The preservation of judicial autonomy had to be constantly taken care of, and the Vilnius city authorities did this by securing confirmatory privileges of self-governance and, if necessary, the ruler’s injunctions against their violation by the Vilnius Palatine and Bishop, whose courts some times violated the judicial autonomy of Vilnius. In this respect, one of the critical moments was the reform of the courts of the Grand Duchy of Lithuania and the renewal of the Statute of Lithuania in the pre-union period (the 1560s). During the reign of Sigismund Augustus, King of Poland and Grand Duke of Lithuania, the City of Vilnius was granted as many as three Confirmation privileges, which renewed the rights of self-governance and ensured the inviolability of the city’s legal autonomy during the period of judicial reform and the adoption of the Second Lithuanian Statute. The last one, on 16 January 1566, crowned the intense struggle of Vilnius citizens during the years of great changes in the Grand Duchy of Lithuania.
Keywords: Vilniaus miestas; savivalda; Magdeburgo teisė; Žygimantas Augustas